Melatonin and gut microbiome - N. E. Garashchenko; N. V. Semenova; L. I. Kolesnikova (Acta Biomedica Scientifica, 2024)
In recent years, studies of the human microbiome have led to the development of the gut-brain axis theory, which proposes a relationship between the gut bacterial community and its metabolites and chemical compounds, as well as physiological and pathological processes in the brain. Melatonin is considered one of the potential links in this relationship.The review provides brief information about the synthesis, metabolism and effects of melatonin in the body. General patterns of the effect of melatonin on the intestinal microbiota under various conditions, such as oral and intraperitoneal melatonin administration, sleep deprivation, as well as the results of studying the microbial community with measurement of hormone levels are considered.Results are presented for families and individual genera of microorganisms and are obtained from studies in animal models or in the research of diseases. The article also notes some additional parameters which are supposed to be relevant to the interaction of melatonin with gut microbiome. Special attention is paid to butyrate as one of the most studied possible parts in this interaction. Studying the relationship between melatonin and microbiome is of interest for basic science and practical medicine.Literature search was carried out using electronic information resources PubMed and eLibrary.